The Understanding of psychological challenges facing South African school learners in the 21st century: a visual explanatory approach - Kanyopa, Theresia Joakim; Mokhele-Makgalwa, Matseliso (Penerbit Universiti Kebangsaan Malaysia, 2024)
The 21st century has brought rapid social, technological, and economic changes that have reshaped the educational landscape worldwide. Within this context, South African school learners face a multifaceted psychological challenge that significantly impacts their well-being and educational outcomes. These challenges are shaped by the unique sociocultural context of South African societies marked by historical inequalities, cultural diversity, and socioeconomic disparities. Thus, this study aimed to explore the understanding of the psychological challenges facing South African learners in the 21st century through the visual explanatory research design. To develop effective interventions and support systems, the study employed a qualitative research approach from the interpretive paradigm perspective to explain the researched issue textually and visually through its participants’ perspectives. The research context and the participants were purposefully and conveniently selected from two secondary schools in the Kwa-Zulu Natal province of South Africa. Besides, the study utilised the focus group discussion and drawing as a visual explanatory approach to generate data. Further, thematic data analysis was used to assign codes and themes. The findings indicate that South African learners are negatively impacted by the psychological challenges that come with the advancement of technology in the 21st century. This study suggests that both parents and the teachers must understand that technology brought both pros and cons to young generations; thus, guidance and restrictions should be employed in the use of technological devices for the benefit and well-being of these learners.